Transposition technique of translating personification in Kahlil Gibran’s novel, The Broken Wings - Tatu Siti Rohbiah; Uup Gufron (Kantor Bahasa Provinsi Banten and Perkumpulan pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya (PPJB-SIP)., 2025)
This research is intended to describe and analyze the transposition technique in translating personification in Kahlil Gibran's novel The Broken Wings, and the factors that cause non-equivalence between the source language (SL) and the Indonesian translation, Sayap-Sayap Patah (TL). This research focuses on identifying grammatical transposition techniques. The researcher uses a qualitative method with content analysis. The study identified 89 examples of personification translation, indicating that transposition techniques play an essential role in achieving equivalence. Examples of this case in class shifts, such as the verb